MCU Upregulation Overactivates Mitophagy by Promoting VDAC1 Dimerization and Ubiquitination in the Hepatotoxicity of Cadmium - Liu, Cong; Li, Hui‐Juan; Duan, Wei‐Xia; Duan, Yu; Yu, Qin; Zhang, Tian; Sun, Ya‐Pei; Li, Yuan‐Yuan; Liu, Yong‐Sheng; Xu, Shang‐Cheng (Advanced science, 2023)
Cadmium (Cd) is a high‐risk pathogenic toxin for hepatic diseases. Excessive mitophagy is a hallmark in Cd‐induced hepatotoxicity. However, the underlying mechanism remains obscure. Mitochondrial calcium uniporter (MCU) is a key regulator for mitochondrial and cellular homeostasis. Here, Cd exposure upregulated MCU expression and increased mitochondrial Ca2+ uptake are found. MCU inhibition through siRNA or by Ru360 significantly attenuates Cd‐induced excessive mitophagy, thereby rescues mitochondrial dysfunction and increases hepatocyte viability. Heterozygous MCU knockout mice exhibit improved liver function, ameliorated pathological damage, less mitochondrial fragmentation, and mitophagy after Cd exposure. Mechanistically, Cd upregulates MCU expression through phosphorylation activation of cAMP‐response element binding protein at Ser133(CREBS133) and subsequent binding of MCU promoter at the TGAGGTCT, ACGTCA, and CTCCGTGATGTA regions, leading to increased MCU gene transcription. The upregulated MCU intensively interacts with voltage‐dependent anion‐selective channel protein 1 (VDAC1), enhances its dimerization and ubiquitination, resulting in excessive mitophagy. This study reveals a novel mechanism, through which Cd upregulates MCU to enhance mitophagy and hepatotoxicity. After cadmium (Cd) exposure, the cytosolic Ca2+‐dependent increases and activation of cAMP‐response element binding protein (CREB) orchestrally upregulates mitochondrial calcium uniporter (MCU) gene transcription, and promotes its translocation into mitochondria. The upregulated MCU in mitochondria directly interacts with voltage‐dependent anion‐selective channel protein 1 (VDAC1) and further enhances the dimerization and ubiquitination of VDAC1, which then overactivates mitophagy and leads to hepatocyte death.